2013
DOI: 10.1186/1471-2350-14-73
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variant m.15218A > G in Finnish epilepsy patients who have maternal relatives with epilepsy, sensorineural hearing impairment or diabetes mellitus

Abstract: BackgroundMitochondrial diseases caused by mutations in mitochondrial DNA (mtDNA) affect tissues with high energy demand. Epilepsy is one of the manifestations of mitochondrial dysfunction when the brain is affected. We have studied here 79 Finnish patients with epilepsy and who have maternal first- or second-degree relatives with epilepsy, sensorineural hearing impairment or diabetes mellitus.MethodsThe entire mtDNA was studied by using conformation sensitive gel electrophoresis and PCR fragments that differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…It indicated that the function of complex I may be associated with IR. Five of the above seven mtDNA variants were found in complex I in our study, which were previously reported in patients with diabetes ( 34 , 38 , 40 , 78 ). It may be due to the influence on the structure and the function of complex I, leading to IR and defecting the function of islets; thereby, these were considered to be possibly diabetes and DKD associated.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It indicated that the function of complex I may be associated with IR. Five of the above seven mtDNA variants were found in complex I in our study, which were previously reported in patients with diabetes ( 34 , 38 , 40 , 78 ). It may be due to the influence on the structure and the function of complex I, leading to IR and defecting the function of islets; thereby, these were considered to be possibly diabetes and DKD associated.…”
Section: Discussionsupporting
confidence: 84%
“…Another variant was the m.A15218G variant in MT-CYB. Previous research associated m.A15218G with epilepsy, diabetes, and Leber hereditary optic neuropathy (LHON) ( 78 , 80 ). This variant led to the substitution of a conserved hydrophilic threonine by a hydrophobic alanine at position 159 of the cytochrome b subunit of complex III.…”
Section: Discussionmentioning
confidence: 99%
“…No variant predicted as deleterious by SIFT and probably damaging by PolyPhen was observed more than 3 times in the 436 samples sequenced, except the polymorphism rs2853506 (A15218G), which was observed in 10 samples (2%). This polymorphism has been found associated with epileptogenesis[ 30 ]. This SNP is located in the gene coding for cytochrome b, MT-CYB .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, polymorphisms that increase the risk of developing two or more diseases were limited to mitochondrial cytochrome b (CYB: H16R, T158A) and subunit 3 of cytochrome c oxidase (COIII: V91L, N154S) genes. The CYB variants H16R and T158A were previously associated with several diseases (31,32). The only non-synonymous polymorphism associated with a reduced risk of various entities was the G10398A (T114A) of ND3, which occurs twice on the human mtDNA phylogeny and has previously been associated with Parkinson's disease and cardiomyopathies (33)(34)(35)(36).…”
Section: Mitochondrial Dna Variants In Human Diseasesmentioning
confidence: 99%